2019
DOI: 10.1002/cctc.201901493
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Sulfur‐Containing Transition Metal (Mn, Fe, Co, and Ni) (Hydr)oxides for Efficient Oxygen Evolution Reaction

Abstract: Transition metal based materials are promising non-noble metal based catalysts for the oxygen evolution reaction (OER). Transition metal (hydr)oxides have been intensively investigated as OER catalysts. Promoting transition metal (hydr)oxides with heteroatoms or using carbon materials as additives can increase the electric conductivity and tailor the nature of active sites to enhance OER activity. We developed a scalable one-step wet chemical method to prepare sulfur-containing transition metal (manganese, iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…24 In addition, non-noble metals can be used to replace noble metals for the electrocatalytic OER. 25,26 Until now, it has been reported that many non-noble metals and their derivatives such as carbides, 27,28 oxides, 29,30 phosphides, 31,32 nitride, 33,34 sulfides 35,36 and so on have been used to prepare OER electrocatalysts, whose behaviors can be compared to those of noble metal catalysts. Based on the further development of the above-mentioned non-precious metal catalysts, bimetal-based catalysts, as a new research frontier in catalysis, have attracted widespread attention due to their excellent electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, non-noble metals can be used to replace noble metals for the electrocatalytic OER. 25,26 Until now, it has been reported that many non-noble metals and their derivatives such as carbides, 27,28 oxides, 29,30 phosphides, 31,32 nitride, 33,34 sulfides 35,36 and so on have been used to prepare OER electrocatalysts, whose behaviors can be compared to those of noble metal catalysts. Based on the further development of the above-mentioned non-precious metal catalysts, bimetal-based catalysts, as a new research frontier in catalysis, have attracted widespread attention due to their excellent electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…oxides and even metal-free systems have been widely studied under alkaline conditions. [5][6][7][8][9][10][11][12] Inspired by nature (Mn-based clusters in PS II), manganese-based materials are especially interesting. 13 Bergman et al 14 as well as Smith et al 15 pointed out in early studies that the electronic properties and structure of the manganese oxides have to be optimized to achieve a superior OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Transition metal oxides (TMOs) and transition metal phosphides (TMPs) have been widely concerned. [28][29][30][31][32] Among them, TMOs are considered as high active electrocatalysts for OER , [33,34] but the activity is difficult to be further improved due to their easy agglomeration in the catalytic process and poor electrical conductivity. [35,36] Researches have shown that the combination of TMOs with conductive substrates such as Ni foam (NF), Ti mesh and carbon cloth (CC) is a feasible approach to improve the electrical conductivity of TMOs.…”
Section: Introductionmentioning
confidence: 99%